2017
DOI: 10.1200/jco.2017.73.6728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Education and Income on Treatment and Outcome in Patients With Acute Myeloid Leukemia in a Tax-Supported Health Care System: A National Population-Based Cohort Study

Abstract: Purpose Previous US studies have shown that socioeconomic status (SES) affects survival in acute myeloid leukemia (AML). However, no large study has investigated the association between education or income and clinical characteristics, treatment, and outcome in AML. Methods To investigate the effects of education and income in a tax-supported health care system, we conducted a population-based study using individual-level SES and clinical data on all Danish patients with AML (2000 to 2014). We compared treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
2
34
1
Order By: Relevance
“…Prior studies have also demonstrated a lower receipt of chemotherapy with increasing age and greater burden of comorbidities [8][9][10][11]13 ( Table 3). Two of the prior studies 8,9 were performed only on Medicare patients aged 65 years or older; hence, these 2 studies do not inform factors associated with the receipt of chemotherapy in younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have also demonstrated a lower receipt of chemotherapy with increasing age and greater burden of comorbidities [8][9][10][11]13 ( Table 3). Two of the prior studies 8,9 were performed only on Medicare patients aged 65 years or older; hence, these 2 studies do not inform factors associated with the receipt of chemotherapy in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 This study had suggested that future studies should explore the role of socioeconomic factors and treatment facility location on leukemia care disparity. The study from Denmark 13 highlighted that the utilization of intensive chemotherapy was lower among older patients, particularly those with lower education and lower income levels. The country has universal healthcare; hence, the study only focused on understanding the effect of education and income levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent qualitative study found that acute leukaemia patients within an outpatient management program expressed a growing desire to understand their long‐term care plan, and they were struggling to construct a new sense of identity (Nissim et al , ). In our outpatient AML programme, we systematically schedule the interaction and counselling with the interdisciplinary staff, which seems of utmost importance to support patients' and relatives adaptation irrespective of effective treatment or failure (Jepsen et al , ) or their underlying socio‐demographic profile (Ostgard et al , ). Likewise, the integration of rehabilitation is necessary to counteract physical decline (Jarden et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…The planned DLI and targeted posttransplant therapy may be effective at preventing relapse, but this study did not include the patients who received these therapies, so we could not evaluate their effects. The addition of social environments and educational history, which are complex factors, may also be beneficial . The outcomes of allo‐HSCT may vary among transplant centers.…”
Section: Discussionmentioning
confidence: 99%